The impacts of cooking and an assessment of indoor air quality in Colorado passive and tightly constructed homes. (15th October 2018) - Militello-Hourigan, Ryan E.; Miller, Shelly L.
Abstract: Low-energy home design is becoming more common in new and retrofitted homes, and energy-efficient designs often sell at a premium [1 ]. Efficiency measures, like tightening the building envelope saves energy, but can impact the indoor air quality (IAQ). We monitored the IAQ of nine tightly constructed homes, one tightly constructed public library, and one conventionally constructed home, and performed a repeatable cooking activity to observe the impact of the fine particulate matter (PM2.5 ) emissions. We compared PM2.5 concentrations from the cooking activity while operating the mechanical ventilation systems at default rates (∼0.1–0.3 h −1 ) and in a temporary boost mode (∼0.3–0.8 h −1 ). We also measured the concentrations of total volatile organic compounds (TVOCs), formaldehyde, radon, and bedroom carbon dioxide (CO2 ) levels. Results show that PM2.5 concentrations were generally low indoors, but cooking drastically increased concentrations, which were slow to decay. No significant difference was found between operating the ventilators at standard rates and utilizing the temporary boost. Completely-mixed flow reactor models of select homes show that installing and using a directly-exhausting range hood reduced peak PM2.5 concentrations by 75% or more. Current ventilation practices in these buildings may not be adequate for these common activities. Formaldehyde was above the California Office of Environmental Health Hazard Assessment (OEHHA) chronic limit of 9 μg/m 3 in all tight buildings with a median concentration of 30 μg/m 3 . CO2 levels in bedrooms exceeded 1000 ppm in six homes, indicating that bedroom ventilation practices were not consistent nor adequate. Highlights: Indoor air quality was monitored in passive and tightly constructed homes in Colorado. Cooking test resulted in 20-min average PM2.5 concentrations between 100 and 500 μg/m 3 . No significant PM2.5 reduction found between default ventilation and short-term boost. CO2 concentrations exceeded 1000 ppm in six of the ten tested homes. Formaldehyde exceeded the California OEHHA chronic limit of 9 μg/m 3 in all buildings.